Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

Solve 2x2 + 3x – 7 = x2 + 5x + 39 for x. A. x=-6 + or - the square root of 82 B. x=-6 + or - 2 with the square root of 17 C. x=1 +or - the square root of 33 D. x= 1 + or - the square root of 47

Mindee Nelson

in Mathematics

follow
followin
1 answer
5 views

1 answer


Jodi Brooks on September 12, 2018

2x2 +3x -7 =x2 +5x +392x2 +3x -7 -x2 -5x -39=0 x 2 - 2x -46 =0(x-1)2 -46 -1 =0(x-1)2 -47=0(x-1)2 = 47x-1= + or - the square root of 47x= 1 + or - the square root of 47


Add you answer